A patterned low internal stress high reflective layer and its preparation method and application

By designing a patterned low internal stress and high reflective layer structure on the photomask plate, using the Si/Ni multi-layer structure, the low-angle grain boundary of the Cr layer and the twin structure of the Ni layer, the problems of large internal stress and high defect density of the existing reflective layer materials are solved, and the coordinated optimization of high reflectivity, low internal stress and excellent stability is achieved.

CN119291821BActive Publication Date: 2025-03-14CHANGSHA SHAOGUANG CHROME BLANK +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411803509.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-14
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing photomask reflective layer materials still face many challenges in meeting the comprehensive performance requirements of high reflectivity, low internal stress, low defect density, excellent stability and controllable patterning characteristics, especially the problems of large internal stress, poor interface bonding force and high defect density.

Method used

A patterned low internal stress high reflective layer structure is adopted, including constructing an n(Si/Ni) layer, a Cr layer, a cap layer and a patterned reflective layer on a γ-Al2O3 substrate. The average thickness ratio is precisely controlled by alternating deposition of the Si layer and the Ni layer, and combining the low-angle grain boundary structure of the Cr layer and the twin structure of the Ni layer, stress management and optical performance optimization are achieved.

Benefits of technology

It significantly reduces the internal stress of the high-reflective layer, improves the stability and service life of the structure, and optimizes the optical performance and patterning characteristics, meeting the performance requirements of the photomask plate in the development of high integration and small line width.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119291821B_ABST
    Figure CN119291821B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of thin film materials, and provides a patterned low internal stress high reflective layer and a preparation method and application thereof, wherein the high reflective layer comprises γ-Al 2 O 3 n(Si / Ni) layer, Cr layer, cap layer, and patterned reflective layer on the substrate; the n(Si / Ni) layer is composed of n cycles of Si layer and Ni layer alternately deposited, and the alternating cycle n is 30-60; the average thickness of the Si layer is 15-40nm, the average thickness of the Ni layer is 3-8nm, and the average thickness ratio of the Si layer to the Ni layer is 5:1; the bottom layer of the n(Si / Ni) layer is a Si layer and is adjacent to the γ-Al 2 O 3 The substrate is connected, and the top layer is a Ni layer. The present invention adopts a multi-layer composite structure design to achieve high reflectivity, low internal stress, low defect density and chemical stability, solving the problems of high internal stress and high defect density in traditional high reflective layers, and can be applied to photolithography masks, optical imaging and sensor fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thin film materials, and in particular to a patterned low internal stress high reflection layer and a preparation method and application thereof. Background Art

[0002] As a key component in the photolithography process, the performance of the reflective layer of the photomask directly affects the manufacturing quality and efficiency of semiconductor devices. In advanced processes, the reflective layer of the photomask must have high reflectivity, low internal stress, excellent chemical stability and thermal stability, and controllable patterning characteristics. High reflectivity ensures efficient use of light energy and improves imaging quality; low internal stress maintains the flatness and structural stability of the reflective layer; chemical and thermal stability determine the anti-pollution ability and service life of the mask in a complex process environment; and controllable patterning characteristics are the basis for the precise transfer of complex integrated circuit graphics. In addition, the reflective layer must also have a low defect density to reduce stray light and pattern defects. High-quality reflective layers that meet these performance requirements can not only significantly improve lithography accuracy and efficiency, but also extend the service life of the mask and reduce production costs, which is of great significance for promoting semiconductor manufacturing to develop towards higher integration and smaller line widths. Therefore, the development of reflective layer materials with high reflectivity, low internal stress, low defect density, excellent stability and controllable patterning characteristics has become the key to the development of photomask technology.

[0003] However, the current photomask reflective layer materials still face many challenges in meeting the above-mentioned comprehensive performance requirements. Although the traditional metal reflective film has a high reflectivity, it has large internal stress, poor interface bonding, and high defect density. Although the multilayer reflective film structure can improve the reflectivity, the interlayer stress accumulation is significant, the thermal stability is poor, and defects are easily formed at the interlayer interface. Although nanocomposites can reduce internal stress to a certain extent, the reflectivity is often insufficient, and the chemical stability and defect control still need to be improved. The root of these problems lies in the fact that the material design fails to achieve an organic combination of stress regulation, interface engineering, defect suppression and structural optimization at the atomic and nanoscale. For example, the Chinese patent with patent number CN113267956A discloses a multilayer reflective film structure for a photomask, but it has the disadvantages of excessive internal stress and high defect density. In addition, existing materials still face difficulties in achieving controllable patterning while maintaining high reflectivity and low internal stress, which limits their application in complex integrated circuit manufacturing. Therefore, developing new types of patterned low-internal stress and high-reflection layer materials to achieve coordinated optimization of reflectivity, internal stress, defect density, stability and patternability has become the focus and difficulty of current photomask technology research and the key to promoting the advancement of semiconductor manufacturing technology. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a patterned low internal stress high reflective layer and its preparation method and application, so as to solve the problems of high internal stress, poor interface bonding and high defect density of the current high reflective layer.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A patterned low internal stress high reflective layer, the high reflective layer comprises γ-Al 2 O 3 n(Si / Ni) layer, Cr layer, cap layer, and patterned reflective layer on the substrate;

[0009] The n (Si / Ni) layer is composed of Si layers and Ni layers deposited alternately for n periods, and the alternating period n is 30 to 60;

[0010] The average thickness of the Si layer is 15-40 nm, the average thickness of the Ni layer is 3-8 nm, and the average thickness ratio of the Si layer to the Ni layer is 5:1; the bottom layer of the n (Si / Ni) layer is a Si layer and is adjacent to the γ-Al 2 O 3 The substrate is connected and the top layer is Ni layer.

[0011] The innovative high-reflection layer structure design of the present invention is intended to enhance the reflective performance and structural stability of the photomask.

[0012] First, the present invention is based on γ-Al 2 O 3 A composite structure consisting of n(Si / Ni) layer and Cr layer is constructed on the substrate. 2 O 3 The choice of substrate provides excellent thermal stability and mechanical strength to the entire reflective layer, which is crucial to withstand the thermal load and mechanical stress during the lithography process.

[0013] Secondly, the n(Si / Ni) layer is formed by alternating epitaxial deposition of Si layers and Ni layers, and the alternating period n is controlled between 30 and 60. The design of this periodic multilayer structure has multiple functions: 1) By precisely controlling the average thickness and period number of the Si layer and the Ni layer, efficient reflection of light of a specific wavelength can be achieved, thereby improving the reflection performance of the photomask and ensuring the accuracy of graphic transfer during the photolithography process. 2) The alternating arrangement of the Si layer and the Ni layer helps to regulate the mechanical properties of the entire structure, especially the distribution and size of the internal stress, which is crucial to maintaining the flatness and stability of the photomask. At the same time, the bottom layer of the n(Si / Ni) layer of the present invention is a Si layer and is closely related to the γ-Al 2 O 3The top layer is the Ni layer. This arrangement order design also has multiple functions: 1) The Si layer as the bottom layer can be connected to the γ-Al 2 O 3 The substrate forms a good interface bonding, improving the adhesion and stability of the entire structure; 2) The Si layer is the bottom layer of the n (Si / Ni) layer, and the Si layer is epitaxially grown from the γ-Al 2 O 3 Substrate growth, which ensures that the Si layer and γ-Al 2 O 3 Both have high chemical stability, and their contact interfaces are not prone to chemical reactions or diffusion, thus ensuring long-term reliability; 3) The Ni layer as the top layer can provide excellent surface properties, including high reflectivity and good corrosion resistance.

[0014] In addition, the present invention adopts the design of Si / Ni layer average thickness ratio based on thermal expansion coefficient matching, which is mainly used to enhance the stress management performance and thermal stability of the high reflective layer of the photomask. This innovative design fully considers the thermal expansion characteristics of Si and Ni materials, and achieves effective reduction of stress in the high reflective layer and optimization of overall performance by accurately controlling the average thickness ratio between layers.

[0015] In the present invention, the average thickness of the Ni layer is precisely controlled within the range of 3-8 nm, while the average thickness of the Si layer is set between 15-40 nm. More importantly, the average thickness ratio of the two is strictly controlled at a ratio of 1:5. This precise average thickness control and ratio design is derived from an in-depth consideration of the thermal expansion coefficients of Si and Ni. The thermal expansion coefficient of Si is about 2.6×10 -6 / K, while the thermal expansion coefficient of Ni is about 13×10 -6 / K. By setting the average thickness ratio of the Ni and Si layers to 1:5, the present invention cleverly balances the stress generated by the two materials during thermal expansion, thereby effectively reducing the internal stress level of the entire multilayer structure. The difference in thermal expansion coefficients is one of the main reasons for the generation of internal stress in multilayer thin film structures. When two different materials are closely combined, they will expand or contract to varying degrees during temperature changes due to the difference in thermal expansion coefficients, and this difference will inevitably lead to stress at the interface. Si has a smaller thermal expansion coefficient, while Ni has a larger thermal expansion coefficient. By accurately controlling their average thickness ratio, the thermal stresses generated by the two layers of material can offset each other when the temperature changes. Specifically, the combination of a thinner Ni layer (larger thermal expansion coefficient) and a thicker Si layer (smaller thermal expansion coefficient) enables the overall structure to reach a state of equilibrium during thermal expansion, significantly reducing the residual stress of the entire structure.

[0016] This design based on thermal expansion coefficient matching not only helps to reduce stress, but also brings a series of performance advantages. First, the multi-layer structure under low stress has higher stability and reliability. During the use of the photomask, it needs to withstand repeated thermal cycles and light exposure. This low-stress design can effectively reduce deformation or damage caused by accumulated thermal stress and extend the service life of the photomask. Secondly, the reduction of stress helps to maintain the flatness of the photomask surface, which is crucial to ensure the accuracy of pattern transfer during the photolithography process.

[0017] In addition, the precise control of the average thickness ratio of the Si layer and the Ni layer also has a positive impact on the optical performance of the entire structure. By adjusting the average thickness of each layer, the reflection and transmission characteristics of light can be optimized, and the reflection efficiency of the reflective layer for light of a specific wavelength can be improved. This optimization of optical performance directly affects the clarity and contrast of the pattern during the lithography process, thereby improving the accuracy of lithography.

[0018] The present invention, by precisely controlling the average thickness ratio of the Si and Ni layers, cleverly utilizes the difference in thermal expansion coefficients of the two materials, further solves the thermal stress problem in the high reflective layer, and optimizes the optical performance. This design not only improves the stability and service life of the photomask, but also provides more reliable technical support for high-precision photolithography processes.

[0019] The Cr layer of the present invention, as a transition layer, can improve the adhesion between the n(Si / Ni) multilayer structure and the upper film, and also has a certain stress buffering effect. At the same time, the Cr layer enhances the mechanical strength of the entire structure, and may also play an optical adjustment role, working in conjunction with the n(Si / Ni) layer, etc., to optimize the overall reflection characteristics.

[0020] The technical solution of the present invention skillfully combines the n(Si / Ni) layer, the Cr layer, the cap layer and the patterned reflective layer, thereby achieving coordinated optimization of optical performance, chemical stability and patterned function.

[0021] Preferably, a strain relaxation interface is contained between the Si layer and the Ni layer;

[0022] The existence of this strain relaxation interface allows moderate strain release while maintaining a certain lattice match between adjacent material layers. This interface structure can not only maintain good interlayer bonding strength, but also effectively alleviate the stress accumulation caused by lattice mismatch, thereby reducing the internal stress level of the entire reflective layer. Low internal stress can not only improve the stability and service life of the photomask, but also ensure high-precision pattern transfer during repeated use.

[0023] Preferably, the Ni layer contains a twin structure, and the twin structure is grown by releasing the interface stress of the strain relaxation interface between the Si layer and the Ni layer; the density of the twin structure is (4-10)×10 7 cm -1 .

[0024] The Ni layer of the present invention contains a twin structure, which can enhance the structural stability and stress release performance of the high reflective layer of the photomask, and further improve the performance of the n (Si / Ni) layer structure. In the present invention, the twin structure in the Ni layer can provide a more effective interface stress release mechanism for the strain relaxation interface between the Si layer and the Ni layer. Twins are a special crystal defect that forms a symmetrical lattice arrangement in the material. This structure can significantly affect the mechanical properties of the material while maintaining the overall performance of the material. The present invention controls the twin density in the Ni layer to be between 10 8 ~10 9 cm -2 The existence of twin structure in Ni layer plays a multi-faceted role in improving the performance of the entire high reflective layer structure.

[0025] First, the twin structure provides an additional channel for the release of interface stress. When stress is generated in the Si layer and the Ni layer due to lattice mismatch, these stresses can be redistributed and partially released through the twin interface, thereby reducing the internal stress level of the entire structure. This stress release mechanism not only helps maintain the stability of the structure, but also reduces the risk of deformation or cracking caused by stress accumulation.

[0026] Secondly, the introduction of the twin structure enhances the plastic deformation ability of the Ni layer. During the use of the photomask, it may face challenges such as thermal cycling and mechanical stress. The existence of the twin structure enables the Ni layer to better adapt to these external environmental changes, absorbing and relieving stress through microscopic plastic deformation, thereby improving the durability and reliability of the entire high-reflectivity layer.

[0027] In addition, the presence of twin structures may also have a positive impact on the optical properties of the Ni layer. Twins may produce a unique scattering effect on the incident light due to their special crystal structure, potentially enhancing the reflective properties of the entire reflective layer or reducing the impact of stray light.

[0028] The twin structure of the Ni layer in the present invention forms a good synergistic effect with the Si / Ni multilayer structure and the strain relaxation interface. The strain relaxation interface provides the basic conditions for stress release; the twin structure in the Ni layer further strengthens this stress release mechanism, so that the entire structure has better mechanical properties and structural stability while maintaining high reflectivity; the precise average thickness ratio design of the n (Si / Ni) layer based on thermal expansion coefficient matching optimizes the stress distribution from the overall structure. The combination of these three stress management mechanisms enables the entire high-reflectivity layer structure to exhibit excellent stability and reliability when facing complex usage environments.

[0029] Preferably, the γ-Al 2 O 3 γ-Al in substrate 2 O 3 The (001) or (111) crystal plane is perpendicular to the γ-Al 2 O 3 Substrate surface;

[0030] The γ-Al 2 O 3 The average surface roughness of the substrate is Ra<2 nm.

[0031] Preferably, the γ-Al 2 O 3 The preparation method of the substrate is as follows: using a Si wafer as the substrate, wherein the Si wafer is a Si(001) wafer or a Si(111) wafer, firstly obtaining a γ-Al on the Si wafer by a molecular beam epitaxy method; 2 O 3 The substrate is then processed by acid etching and chemical mechanical polishing to obtain γ-Al 2 O 3 substrate;

[0032] The preparation parameters of the molecular beam epitaxy method are as follows: at 600-750°C, with Al as the target material, with a flow rate of 30-60 sccm and a purity of 99.99% oxygen as the reaction atmosphere, a radio frequency plasma source power of 50-100 W, and a working pressure of (1-5)×10 -4 Pa, to obtain γ-Al on Si wafer 2 O 3 substrate;

[0033] The acid etching comprises the following steps: 2 O 3 The substrate is placed in a hydrofluoric acid solution with a mass fraction of 50-55% to etch the Si wafer. After the etching is completed, the γ-Al 2 O 3The substrate was cleaned with deionized water for three times and finally dried completely under vacuum at room temperature.

[0034] The present invention uses γ-Al 2 O 3 As a substrate material, the (001) or (111) crystal plane is specifically specified to be perpendicular to the substrate surface, providing an ideal crystallographic basis for subsequent thin film growth. This specific crystal plane orientation helps promote the epitaxial growth of n(Si / Ni) multilayer structures, thereby improving the crystallization quality and interface characteristics of the overall structure.

[0035] In the present invention, γ-Al 2 O 3 The average surface roughness Ra of the substrate is strictly controlled to be less than 2nm, which is crucial for the preparation of high-quality thin films. A flat substrate surface can ensure good uniformity and continuity of the subsequent deposited functional layers, especially enabling the Si layer (as the first layer of the n(Si / Ni) structure) to grow uniformly, reducing the generation of defects, thereby improving the performance and reliability of the entire structure.

[0036] Preferably, the average thickness of the Cr layer is 20-60 nm; the Cr layer contains low-angle grain boundaries; and the content of the low-angle grain boundaries in the Cr layer is 45-65 vol%.

[0037] The Cr layer of the present invention contains 45-65 vol% of low-angle grain boundaries, and the microstructure has multiple functions: 1) the low-angle grain boundaries can effectively release the stress inside the film and improve the stability of the entire structure; 2) this grain boundary structure can enhance the mechanical strength of the Cr layer and improve the durability of the photomask; 3) the low-angle grain boundaries may also produce a special scattering effect on the incident light, which helps to optimize the optical performance. In addition, the average thickness of the Cr layer is controlled within the range of 20-60 nm. The selection of this average thickness range not only ensures that the function of the Cr layer is fully exerted, but also does not excessively affect the optical properties of the entire structure.

[0038] Preferably, the capping layer is RuNb, and the average thickness of the capping layer is 2-8 nm;

[0039] The patterned reflective layer is CrCON, and the average thickness of the patterned reflective layer is 4-10 nm.

[0040] The design objectives of the cap layer of the present invention are mainly three aspects: first, as a protective layer, it effectively isolates the influence of the external environment on the n (Si / Ni) layer and the Cr layer, and improves the chemical stability and durability of the system; second, by utilizing the characteristics of Ru-based alloys, while maintaining high reflectivity, the electrical and chemical properties of the surface are further optimized; third, it provides ideal interface conditions for the subsequent deposition of a patterned reflective layer.

[0041] The present invention designs a graphic reflective layer on top of the cap layer, and the material is CrCON. First, CrCON is an excellent low-reflective material that can effectively reduce the reflectivity within a specific wavelength range. Secondly, the material has good chemical stability and mechanical strength, which further enhances the durability of the entire structure. Most importantly, by designing the low-reflective layer as a graphic structure, the spatial selectivity of the optical performance is achieved. This design allows high-reflective areas and low-reflective areas to exist on the same optical element at the same time, greatly expanding the application range and functionality of the device.

[0042] While ensuring high reflective performance, the present invention also achieves improved chemical stability and spatial regulation of optical performance. It is particularly noteworthy that by precisely controlling the average thickness and composition of each layer, fine adjustment of performance can be achieved at the nanoscale. For example, the average thickness of the cap layer is controlled at 2~8nm, which can not only play a protective role, but also will not significantly affect the overall optical performance. Similarly, the average thickness range of the low-reflective layer of 4~10nm allows the film properties of the overall structure to be maintained while ensuring the low-reflective effect. The diversity of material selection also provides greater flexibility for performance optimization. For example, RuNb as a cap layer material, the most suitable combination can be selected according to specific application requirements to balance chemical stability, conductivity and optical performance. Similarly, CrCON as a low-reflective layer material can also be selected according to target wavelength and environmental requirements. The design of the multi-layer composite structure of the present invention not only solves the limitations of traditional single-function optical films, but also provides a new technical path for micro-nano processing and integration of optical devices.

[0043] In general, the present invention cleverly solves the stress problem in the high reflective layer, the interface stability problem and the optical performance optimization problem through a carefully designed multilayer structure. This comprehensive design not only improves the stability and service life of the photomask, but also provides more reliable technical support for high-precision photolithography. Through the synergistic effect of each functional layer, the present invention achieves comprehensive optimization of structural stability, interface adhesion, stress management, thermal stability and optical performance.

[0044] The present invention provides a method for preparing a patterned low internal stress high reflective layer, comprising the following steps:

[0045] S1, γ-Al 2 O 3 The substrate was first cleaned by ultrasonic cleaning, then cleaned with acetone and deionized water, and finally dried with high-purity nitrogen. 2 O 3 Substrate surface: Ultrasonic cleaning and high-purity nitrogen drying further ensure the cleanliness of the substrate surface, creating conditions for good adhesion and uniform growth of the film;

[0046] S2, the γ-Al obtained in step S1 2 O 3 The substrate is placed in an ultra-high vacuum magnetron sputtering system with a basic vacuum degree of less than 5×10 -8 Torr, the chamber temperature is 25 ± 2°C;

[0047] S3, magnetron sputtering method, on γ-Al 2 O 3 Si layers and Ni layers are alternately deposited on the substrate, and the number of alternating deposition cycles is n, forming n (Si / Ni) layers;

[0048] S4, preparing a Cr layer on the n(Si / Ni) layer by magnetron sputtering;

[0049] S5, preparing a cap layer on the Cr layer by magnetron sputtering;

[0050] S6. Prepare a reflective layer to be patterned on the cap layer by magnetron sputtering, then coat and pattern the reflective layer to be patterned with photoresist, and then etch the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer; and then perform vacuum annealing at 200-250° C. for 1 hour.

[0051] Preferably, the preparation parameters of the Si layer in step S3 are: using Si with a purity of 99.999% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 15-40 sccm, and the sputtering power density to 1.5-3.0 W / cm 2 ;Deposition rate is 0.20~0.50 nm / s;

[0052] The preparation parameters of the Ni layer in step S3 are: using Ni with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 25-60 sccm, and the power density to 2.0-4.0 W / cm 2 ;Deposition rate is 0.15~0.30nm / s;

[0053] The preparation parameters of the Cr layer in step S4 are: using Cr with a purity of 99.95% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 20-40 sccm, and the power density to 3.0-6.0 W / cm 2 ; The deposition rate is 0.50~0.90 nm / s.

[0054] Preferably, the preparation parameters of the cap layer in step S5 are: using RuNb with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 20-45 sccm, the sputtering power to 100-200 W; the deposition rate to 0.05-0.20 nm / s, the sputtering working pressure to 0.5-1.5 Pa, and the sputtering temperature to 120-180°C;

[0055] The preparation method of the reflective layer to be patterned in step S6 is: adopting a magnetron sputtering method, using Cr with a purity of 99.95% as a target material, and using a mixed gas of argon with a purity of 99.999%, nitrogen with a purity of 99.999%, oxygen with a purity of 99.999% and methane with a purity of 99.999% as an atmosphere, wherein the volume ratio of argon, nitrogen, oxygen and methane is 4:1:1:0.5, the flow rate of the mixed gas is 25~50sccm, the sputtering power is 150~300W, the sputtering working pressure is 0.5~1.5Pa, the sputtering temperature is 150~200℃, and the substrate bias is 10~35V.

[0056] In the preparation process of the present invention, the method adopts an ultra-high vacuum magnetron sputtering system and accurately controls various process parameters, such as vacuum degree, temperature, gas flow rate, power density and deposition rate. The precise control of these parameters ensures the high controllability and repeatability of film growth, which is the key to achieving high-quality film structure. Especially in the preparation of Si, Ni and Cr layers, by adjusting the high-purity argon gas flow rate and power density, the growth rate and quality of the film can be accurately controlled, thereby optimizing the microstructure and performance of the film. Finally, the annealing step further optimizes the performance of the entire structure. Annealing under appropriate temperature and vacuum conditions can promote the rearrangement of atoms inside the film and the improvement of the interface, which is conducive to reducing internal stress, improving structural stability and optical properties.

[0057] In addition, the present invention also provides the use of the above-mentioned patterned low internal stress high reflection layer or the patterned low internal stress high reflection layer prepared by the above-mentioned preparation method in the field of photolithography mask, optical imaging or sensor.

[0058] (3) Beneficial technical effects:

[0059] 1. The patterned low internal stress high reflective layer of the present invention brings significant performance improvement to the photomask. The innovative multi-layer structure cleverly solves the problems of insufficient reflectivity and excessive internal stress of the traditional high reflective layer. 2 O 3 The substrate provides an ideal growth foundation for n(Si / Ni) multilayer structures, improving the crystal quality and interface properties, and the γ-Al 2 O 3The substrate has thermal stability and mechanical strength; the periodic design of the n(Si / Ni) layer achieves efficient reflection and regulates the internal stress distribution; the Cr layer further enhances the structural stability.

[0060] 2. The present invention contains a strain relaxation interface between the Si layer and the Ni layer, which balances the lattice matching and strain release, significantly reducing the internal stress. And by introducing a twin structure in the Ni layer, the performance of the high reflective layer of the photomask is comprehensively improved. The twin density is controlled at (4~10)×10 7 cm -1 Within the range, it provides an additional stress release channel for the Si / Ni interface, effectively reducing the internal stress level, which forms a synergistic effect with the strain relaxation interface, significantly enhancing the structural stability and durability while maintaining high reflectivity. In addition, the twin structure also improves the plastic deformation ability of the Ni layer, making the high reflectivity layer more adaptable to thermal cycles and mechanical stress. This innovative design idea from micro to macro not only solves the stress problem in traditional technology, but also potentially enhances optical performance.

[0061] 3. The present invention achieves comprehensive optimization of the performance of the high reflective layer of the photomask through a carefully designed multilayer structure. The average thickness ratio of the Si / Ni layer is based on the principle of thermal expansion coefficient matching, and forms a triple stress management mechanism with the twin structure and strain relaxation interface, which significantly improves the structural stability and reliability. The special arrangement order of the n(Si / Ni) layer further optimizes the interface adhesion and optical performance: the bottom Si layer and the γ-Al 2 O 3 The substrate forms a stable interface, and the top Ni layer provides high reflectivity and corrosion resistance. This multi-level and multi-dimensional design concept fully reflects the concept of advanced material engineering and achieves the coordinated optimization of optical performance, thermal stability and structural reliability.

[0062] 4. The present invention achieves the coordinated optimization of optical performance, chemical stability and graphic function through a carefully designed multi-layer composite structure. The high reflective layer provides excellent reflection characteristics, the nanoscale capping layer enhances chemical stability, and the graphic reflective layer realizes spatial regulation of optical performance. The precise control of the average thickness and composition of each component enables fine adjustment of performance at the nanoscale. The special low-angle grain boundary structure of the Cr layer effectively releases stress and improves mechanical strength. γ-Al 2 O 3 The extremely low average surface roughness of the substrate ensures the high-quality growth of subsequent thin films. This multi-layer design not only solves the limitations of traditional single-function optical films, but also provides a new technical path for micro-nano processing and integration of optical devices, which is expected to have an important impact in fields such as semiconductor manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1This is a transmission electron microscope photograph of the n(Si / Ni) layer prepared in Example 1 of the present invention.

[0064] Figure 2 The γ-Al prepared in Example 1 of the present invention 2 O 3 Phase analysis XRD patterns of substrate and n(Si / Ni) layer.

[0065] Figure 3 This is a transmission electron microscope morphology image of the Si / Ni interface in the n(Si / Ni) layer prepared in Example 1 of the present invention.

[0066] Figure 4 This is a strain diagram of the Si / Ni interface in the n(Si / Ni) layer prepared in Example 1 of the present invention.

[0067] Figure 5 This is a transmission electron microscope photograph of the twins of the Ni layer in the n(Si / Ni) layer prepared in Example 1 of the present invention.

[0068] Figure 6 This is an EBSD image of the low-angle grain boundary of the Cr layer prepared in Example 1 of the present invention.

[0069] Figure 7 The γ-Al of Example 1 of the present invention 2 O 3 The average surface roughness of the substrate.

[0070] Figure 8 This is a strain diagram of the Si / Ni interface in the n(Si / Ni) layer prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0071] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Example 1

[0072] A patterned low internal stress high reflective layer, comprising: 2 O 3 n(Si / Ni) layer, Cr layer, cap layer, and patterned reflective layer on the substrate;

[0073] The n(Si / Ni) layer is composed of 30 cycles of alternating Si and Ni layers; the average thickness of the Si layer is 15nm, and the average thickness of the Ni layer is 3nm; the bottom layer of the n(Si / Ni) layer is the Si layer and is adjacent to the γ-Al 2 O 3The substrate is connected, and the top layer is the Ni layer; there is a strain relaxation interface between the Si layer and the Ni layer; the Ni layer contains a twin structure, and the twin structure is grown by the interface stress release of the strain relaxation interface between the Si layer and the Ni layer; the density of the twin structure is 4×10 7 cm -1 .

[0074] The average thickness of the Cr layer is 20 nm; the Cr layer contains low-angle grain boundaries; the content of low-angle grain boundaries in the Cr layer is 45 vol%.

[0075] The capping layer is RuNb with an average thickness of 2 nm; the patterned reflective layer is CrCON with an average thickness of 4 nm.

[0076] γ-Al 2 O 3 γ-Al in substrate 2 O 3 The (001) crystal plane is perpendicular to the γ-Al 2 O 3 Substrate surface. γ-Al 2 O 3 The average surface roughness Ra of the substrate is 1 nm.

[0077] γ-Al 2 O 3 The preparation method of the substrate is as follows: using a Si wafer as the substrate, the Si wafer is a Si(001) wafer, firstly obtaining a γ-Al on the Si wafer by a molecular beam epitaxy method, 2 O 3 The substrate is then processed by acid etching and chemical mechanical polishing to obtain γ-Al 2 O 3 substrate;

[0078] The preparation parameters of the molecular beam epitaxy method are as follows: at 600 °C, with Al as the target material, with a flow rate of 30 sccm and a purity of 99.99% oxygen as the reaction atmosphere, a radio frequency plasma source power of 50 W, and a working pressure of 1×10 -4 Pa, to obtain γ-Al on Si wafer 2 O 3 substrate;

[0079] Acid etching includes the following steps: 2 O 3 The substrate is placed in a 50% hydrofluoric acid solution to etch the Si wafer. After the etching is completed, the γ-Al 2 O 3 The substrate was cleaned with deionized water for three times and finally dried completely under vacuum at room temperature.

[0080] The method for preparing the patterned low internal stress high reflective layer in this embodiment includes the following steps:

[0081] S1, γ-Al 2 O 3 The substrate was first cleaned by ultrasonic cleaning, then cleaned with acetone and deionized water, and finally dried with high-purity nitrogen. 2 O 3 Substrate surface.

[0082] S2, the γ-Al obtained in step S1 2 O 3 The substrate is placed in an ultra-high vacuum magnetron sputtering system with a basic vacuum degree of less than 5×10 -8 Torr, the chamber temperature is 25±2°C.

[0083] S3, magnetron sputtering method, on γ-Al 2 O 3 Si layers and Ni layers are alternately deposited on the substrate in sequence, with the number of alternating deposition cycles being 30, to form an n (Si / Ni) layer.

[0084] The preparation parameters of the Si layer are as follows: Si with a purity of 99.999% is used as the target material, the flow rate of 99.999% high-purity argon is adjusted to 15sccm, and the sputtering power density is 1.5W / cm 2 ;Deposition rate is 0.20nm / s;

[0085] The preparation parameters of the Ni layer are as follows: using Ni with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 25sccm, and the power density to 2.0W / cm 2 ; The deposition rate is 0.15nm / s.

[0086] S4, preparing a Cr layer on the n(Si / Ni) layer by magnetron sputtering;

[0087] The preparation parameters of the Cr layer are: using Cr with a purity of 99.95% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 20sccm, and the power density to 3.0W / cm 2 ; The deposition rate is 0.50 nm / s.

[0088] S5, preparing a cap layer on the Cr layer by magnetron sputtering;

[0089] The preparation parameters of the cap layer are as follows: using RuNb with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 20sccm, and the sputtering power to 100W; the deposition rate is 0.05nm / s, the sputtering working pressure is 0.5Pa, and the sputtering temperature is 120°C.

[0090] S6, using magnetron sputtering to prepare a reflective layer to be patterned on the cap layer, then coating and patterning the reflective layer to be patterned with a photoresist, and then etching the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer; then performing vacuum annealing at 200° C. for 1 h (vacuum degree <1×10 -6 Torr).

[0091] The preparation method of the reflective layer to be patterned is as follows: using a magnetron sputtering method, using Cr with a purity of 99.95% as a target material, and using a mixed gas of argon with a purity of 99.999%, nitrogen with a purity of 99.999%, oxygen with a purity of 99.999% and methane with a purity of 99.999% as an atmosphere, wherein the volume ratio of argon, nitrogen, oxygen and methane is 4:1:1:0.5, the flow rate of the mixed gas is 25sccm, the sputtering power is 150W, the sputtering working pressure is 0.5Pa, the sputtering temperature is 150°C, and the substrate bias is 10V.

[0092] The present invention has powerfully demonstrated the structural characteristics and performance advantages of the prepared material through a series of experimental results. Figure 1 The transmission electron microscope photograph clearly shows the layered structure of the n(Si / Ni) layer in Example 1, wherein the average thickness ratio of the Si layer to the Ni layer is 5:1. Figure 2 XRD pattern analysis confirmed that γ-Al 2 O 3 The phase composition of the substrate and n(Si / Ni) layer indicates that the expected crystal structure was successfully obtained during the preparation process. Figure 3 The transmission electron microscopy morphology reveals that the Si / Ni interface contains a strain relaxation interface, which is beneficial to improving the stability of the material. Figure 4 The GPA analysis results of the interface strain show that the strain is almost zero, proving that the interface has low stress characteristics, which has a positive impact on the reliability and service life of the material. Figure 5 The transmission electron microscopy photographs captured the twin structure in the Ni layer, the formation of which can be attributed to the induced effect of interface strain release, further confirming the stress regulation mechanism of the material at the microscale. Figure 6 The large number of red lines observed in the EBSD image represent low-angle grain boundaries, confirming the ubiquitous existence of low-angle grain boundaries in the Cr layer. This structural feature may have a significant impact on the mechanical properties of the material. Figure 7 is the γ-Al in Example 1 2 O 3 The average surface roughness of the substrate is 1 nm, which provides an excellent structural basis for the subsequent preparation of the high-reflection layer. Example 2

[0093] A patterned low internal stress high reflective layer, comprising: 2 O 3 n(Si / Ni) layer, Cr layer, cap layer, and patterned reflective layer on the substrate;

[0094] The n(Si / Ni) layer is composed of 39 cycles of alternating Si and Ni layers; the average thickness of the Si layer is 20 nm, and the average thickness of the Ni layer is 4 nm; the bottom layer of the n(Si / Ni) layer is the Si layer and is adjacent to the γ-Al 2 O 3 The substrate is connected, and the top layer is the Ni layer; there is a strain relaxation interface between the Si layer and the Ni layer; the Ni layer contains a twin structure, and the twin structure is grown by the interface stress release of the strain relaxation interface between the Si layer and the Ni layer; the density of the twin structure is 5.7×10 7 cm -1 .

[0095] The average thickness of the Cr layer is 32 nm; the Cr layer contains low-angle grain boundaries; the content of low-angle grain boundaries in the Cr layer is 50 vol%.

[0096] The capping layer is RuNb with an average thickness of 3 nm; the patterned reflective layer is CrCON with an average thickness of 6 nm.

[0097] γ-Al 2 O 3 γ-Al in substrate 2 O 3 The (111) crystal plane is perpendicular to the γ-Al 2 O 3 Substrate surface. γ-Al 2 O 3 The average surface roughness Ra of the substrate is 1.2 nm.

[0098] γ-Al 2 O 3 The preparation method of the substrate is as follows: using a Si wafer as the substrate, the Si wafer is a Si(111) wafer, firstly obtaining a γ-Al on the Si wafer by a molecular beam epitaxy method, 2 O 3 The substrate is then processed by acid etching and chemical mechanical polishing to obtain γ-Al 2 O 3 substrate;

[0099] The preparation parameters of the molecular beam epitaxy method are: at 645°C, with Al as the target material, with a flow rate of 39sccm and a purity of 99.99% oxygen as the reaction atmosphere, a radio frequency plasma source power of 65W, and a working pressure of 2.2×10 -4 Pa, to obtain γ-Al on Si wafer2 O 3 substrate;

[0100] Acid etching includes the following steps: 2 O 3 The substrate is placed in a 50% hydrofluoric acid solution to etch the Si wafer. After the etching is completed, the γ-Al 2 O 3 The substrate was cleaned with deionized water for three times and finally dried completely under vacuum at room temperature.

[0101] The method for preparing the patterned low internal stress high reflective layer in this embodiment includes the following steps:

[0102] S1, γ-Al 2 O 3 The substrate was first cleaned by ultrasonic cleaning, then cleaned with acetone and deionized water, and finally dried with high-purity nitrogen. 2 O 3 Substrate surface.

[0103] S2, the γ-Al obtained in step S1 2 O 3 The substrate is placed in an ultra-high vacuum magnetron sputtering system with a basic vacuum degree of less than 5×10 -8 Torr, the chamber temperature is 25±2°C.

[0104] S3, magnetron sputtering method, on γ-Al 2 O 3 Si layers and Ni layers are alternately deposited on the substrate in sequence, with the number of alternating deposition cycles being 39, to form an n (Si / Ni) layer.

[0105] The preparation parameters of the Si layer are as follows: Si with a purity of 99.999% was used as the target material, the flow rate of 99.999% high-purity argon was adjusted to 23 sccm, and the sputtering power density was 1.9 W / cm 2 ;Deposition rate is 0.29nm / s;

[0106] The preparation parameters of the Ni layer are as follows: using 99.99% pure Ni as the target material, adjusting the flow rate of 99.999% high-purity argon to 36ccm, and the power density to 2.6W / cm 2 ; The deposition rate is 0.20nm / s.

[0107] S4, preparing a Cr layer on the n(Si / Ni) layer by magnetron sputtering;

[0108] The preparation parameters of the Cr layer are: using Cr with a purity of 99.95% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 26sccm, and the power density to 3.9W / cm 2; The deposition rate is 0.62nm / s.

[0109] S5, preparing a cap layer on the Cr layer by magnetron sputtering;

[0110] The preparation parameters of the capping layer are as follows: using RuNb with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 30sccm, and the sputtering power to 125W; the deposition rate is 0.10nm / s, the sputtering working pressure is 1.0Pa, and the sputtering temperature is 140°C.

[0111] S6, using magnetron sputtering to prepare a reflective layer to be patterned on the cap layer, then coating and patterning the reflective layer to be patterned with a photoresist, and then etching the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer; then performing vacuum annealing at 215° C. for 1 h (vacuum degree <1×10 -6 Torr).

[0112] The preparation method of the reflective layer to be patterned is as follows: using a magnetron sputtering method, using Cr with a purity of 99.95% as a target material, and using a mixed gas of argon with a purity of 99.999%, nitrogen with a purity of 99.999%, oxygen with a purity of 99.999% and methane with a purity of 99.999% as an atmosphere, wherein the volume ratio of argon, nitrogen, oxygen and methane is 4:1:1:0.5, the flow rate of the mixed gas is 30sccm, the sputtering power is 200W, the sputtering working pressure is 0.9Pa, the sputtering temperature is 160°C, and the substrate bias is 15V. Example 3

[0113] A patterned low internal stress high reflective layer, comprising: 2 O 3 n(Si / Ni) layer, Cr layer, cap layer, and patterned reflective layer on the substrate;

[0114] The n(Si / Ni) layer is composed of 48 cycles of alternating Si and Ni layers; the average thickness of the Si layer is 30nm, and the average thickness of the Ni layer is 6nm; the bottom layer of the n(Si / Ni) layer is the Si layer and is adjacent to the γ-Al 2 O 3 The substrate is connected, and the top layer is the Ni layer; there is a strain relaxation interface between the Si layer and the Ni layer; the Ni layer contains a twin structure, and the twin structure is grown by the interface stress release of the strain relaxation interface between the Si layer and the Ni layer; the density of the twin structure is 8×10 7 cm -1 .

[0115] The average thickness of the Cr layer is 44 nm; the Cr layer contains low-angle grain boundaries; the content of low-angle grain boundaries in the Cr layer is 60 vol%.

[0116] The capping layer is RuNb with an average thickness of 5.6 nm; the patterned reflective layer is CrCON with an average thickness of 7.6 nm.

[0117] γ-Al 2 O 3 γ-Al in substrate 2 O 3 The (001) crystal plane is perpendicular to the γ-Al 2 O 3 Substrate surface. γ-Al 2 O 3 The average surface roughness Ra of the substrate is 1.6 nm.

[0118] γ-Al 2 O 3 The preparation method of the substrate is as follows: using a Si wafer as the substrate, the Si wafer is a Si(001) wafer or a Si(111) wafer, firstly obtaining a γ-Al on the Si wafer by a molecular beam epitaxy method, 2 O 3 The substrate is then processed by acid etching and chemical mechanical polishing to obtain γ-Al 2 O 3 substrate;

[0119] The preparation parameters of the molecular beam epitaxy method are: at 690 ° C, with Al as the target material, with a flow rate of 48 sccm and a purity of 99.99% oxygen as the reaction atmosphere, a radio frequency plasma source power of 80 W, and a working pressure of 3.4×10 -4 Pa, to obtain γ-Al on Si wafer 2 O 3 substrate;

[0120] Acid etching includes the following steps: 2 O 3 The substrate is placed in a 50% hydrofluoric acid solution to etch the Si wafer. After the etching is completed, the γ-Al 2 O 3 The substrate was cleaned with deionized water for three times and finally dried completely under vacuum at room temperature.

[0121] The method for preparing the patterned low internal stress high reflective layer in this embodiment includes the following steps:

[0122] S1, γ-Al 2 O 3 The substrate was first cleaned by ultrasonic cleaning, then cleaned with acetone and deionized water, and finally dried with high-purity nitrogen. 2 O 3 Substrate surface.

[0123] S2, the γ-Al obtained in step S1 2 O 3 The substrate is placed in an ultra-high vacuum magnetron sputtering system with a basic vacuum degree of less than 5×10 -8 Torr, the chamber temperature is 25±2°C.

[0124] S3, magnetron sputtering method, on γ-Al 2 O 3 Si layers and Ni layers are alternately deposited on the substrate in sequence, with the number of alternating deposition cycles being 48, to form an n (Si / Ni) layer.

[0125] The preparation parameters of the Si layer are as follows: Si with a purity of 99.999% is used as the target material, the flow rate of 99.999% high-purity argon is adjusted to 30sccm, and the sputtering power density is 2.4W / cm 2 ;Deposition rate is 0.38 nm / s;

[0126] The preparation parameters of the Ni layer are as follows: using Ni with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 46 sccm, and the power density to 3.2 W / cm 2 ; The deposition rate is 0.24nm / s.

[0127] S4, preparing a Cr layer on the n(Si / Ni) layer by magnetron sputtering;

[0128] The preparation parameters of the Cr layer are: using 99.95% pure Cr as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 32sccm, and the power density to 4.8W / cm 2 ; The deposition rate is 0.74nm / s.

[0129] S5, preparing a cap layer on the Cr layer by magnetron sputtering;

[0130] The preparation parameters of the capping layer are as follows: using RuNb with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 40sccm, and the sputtering power to 180W; the deposition rate is 0.15nm / s, the sputtering working pressure is 1.2Pa, and the sputtering temperature is 160°C.

[0131] S6, using magnetron sputtering to prepare a reflective layer to be patterned on the cap layer, then coating and patterning the reflective layer to be patterned with a photoresist, and then etching the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer; then performing vacuum annealing at 230° C. for 1 h (vacuum degree <1×10 -6 Torr).

[0132] The preparation method of the reflective layer to be patterned is as follows: using a magnetron sputtering method, using Cr with a purity of 99.95% as a target material, and using a mixed gas of argon with a purity of 99.999%, nitrogen with a purity of 99.999%, oxygen with a purity of 99.999% and methane with a purity of 99.999% as an atmosphere, wherein the volume ratio of argon, nitrogen, oxygen and methane is 4:1:1:0.5, the flow rate of the mixed gas is 45sccm, the sputtering power is 250W, the sputtering working pressure is 1.2Pa, the sputtering temperature is 180°C, and the substrate bias is 30V. Example 4

[0133] A patterned low internal stress high reflective layer, comprising: 2 O 3 n(Si / Ni) layer, Cr layer, cap layer, and patterned reflective layer on the substrate;

[0134] The n(Si / Ni) layer is composed of 60 cycles of alternate deposition of Si and Ni layers; the average thickness of the Si layer is 40nm, and the average thickness of the Ni layer is 8nm; the bottom layer of the n(Si / Ni) layer is the Si layer and is adjacent to the γ-Al 2 O 3 The substrate is connected, and the top layer is the Ni layer; there is a strain relaxation interface between the Si layer and the Ni layer; the Ni layer contains a twin structure, and the twin structure is grown by the interface stress release of the strain relaxation interface between the Si layer and the Ni layer; the density of the twin structure is 10×10 7 cm -1 .

[0135] The average thickness of the Cr layer is 60 nm; the Cr layer contains low-angle grain boundaries; the content of the low-angle grain boundaries in the Cr layer is 65 vol%.

[0136] The capping layer is RuNb with an average thickness of 8 nm; the patterned reflective layer is CrCON with an average thickness of 10 nm.

[0137] γ-Al 2 O 3 γ-Al in substrate 2 O 3 The (111) crystal plane is perpendicular to the γ-Al 2 O 3 Substrate surface. γ-Al 2 O 3 The average surface roughness Ra of the substrate is 1.8 nm.

[0138] γ-Al 2 O 3The preparation method of the substrate is as follows: using a Si wafer as the substrate, the Si wafer is a Si(111) wafer, firstly obtaining a γ-Al on the Si wafer by a molecular beam epitaxy method, 2 O 3 The substrate is then processed by acid etching and chemical mechanical polishing to obtain γ-Al 2 O 3 substrate;

[0139] The preparation parameters of the molecular beam epitaxy method are: at 750 ° C, with Al as the target material, with a flow rate of 60 sccm and a purity of 99.99% oxygen as the reaction atmosphere, a radio frequency plasma source power of 100 W, and a working pressure of 5×10 -4 Pa, to obtain γ-Al on Si wafer 2 O 3 substrate;

[0140] Acid etching includes the following steps: 2 O 3 The substrate is placed in a 50% hydrofluoric acid solution to etch the Si wafer. After the etching is completed, the γ-Al 2 O 3 The substrate was cleaned with deionized water for three times and finally dried completely under vacuum at room temperature.

[0141] The method for preparing the patterned low internal stress high reflective layer in this embodiment includes the following steps:

[0142] S1, γ-Al 2 O 3 The substrate was first cleaned by ultrasonic cleaning, then cleaned with acetone and deionized water, and finally dried with high-purity nitrogen. 2 O 3 Substrate surface.

[0143] S2, the γ-Al obtained in step S1 2 O 3 The substrate is placed in an ultra-high vacuum magnetron sputtering system with a basic vacuum degree of less than 5×10 -8 Torr, the chamber temperature is 25±2°C.

[0144] S3, magnetron sputtering method, on γ-Al 2 O 3 Si layers and Ni layers are alternately deposited on the substrate in sequence, with the number of alternating deposition cycles being 60, to form an n (Si / Ni) layer.

[0145] The preparation parameters of the Si layer are as follows: Si with a purity of 99.999% was used as the target material, the flow rate of 99.999% high-purity argon was adjusted to 40 sccm, and the sputtering power density was 3.0 W / cm 2;Deposition rate is 0.50 nm / s;

[0146] The preparation parameters of the Ni layer are as follows: using Ni with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 60 sccm, and the power density to 4.0 W / cm 2 ; The deposition rate is 0.30nm / s.

[0147] S4, preparing a Cr layer on the n(Si / Ni) layer by magnetron sputtering;

[0148] The preparation parameters of the Cr layer are: using 99.95% pure Cr as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 40sccm, and the power density to 6.0W / cm 2 ; The deposition rate is 0.90 nm / s.

[0149] S5, preparing a cap layer on the Cr layer by magnetron sputtering;

[0150] The preparation parameters of the cap layer are as follows: using RuNb with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 45sccm, and the sputtering power to 200W; the deposition rate is 0.20 nm / s, the sputtering working pressure is 1.5Pa, and the sputtering temperature is 180℃.

[0151] S6, using magnetron sputtering to prepare a reflective layer to be patterned on the cap layer, then coating and patterning the reflective layer to be patterned with a photoresist, and then etching the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer; then performing vacuum annealing at 250° C. for 1 h (vacuum degree <1×10 -6 Torr).

[0152] The preparation method of the reflective layer to be patterned is as follows: using a magnetron sputtering method, using Cr with a purity of 99.95% as a target material, and using a mixed gas of argon with a purity of 99.999%, nitrogen with a purity of 99.999%, oxygen with a purity of 99.999% and methane with a purity of 99.999% as an atmosphere, wherein the volume ratio of argon, nitrogen, oxygen and methane is 4:1:1:0.5, the flow rate of the mixed gas is 50sccm, the sputtering power is 300W, the sputtering working pressure is 1.5Pa, the sputtering temperature is 200°C, and the substrate bias is 35V.

[0153] Comparative Example 1:

[0154] It is basically the same as Example 1, except that γ-Al 2 O 3 The substrate is a randomly oriented substrate.

[0155] Comparative Example 2:

[0156] It is basically the same as Example 1, except that γ-Al 2 O 3 The average surface roughness Ra of the substrate is 10 nm.

[0157] Comparative Example 3:

[0158] It is basically the same as Example 1, except that the average thickness of the Si layer and the Ni layer are both 15 nm, and the average thickness of the Si layer and the Ni layer is 1:1. Figure 8 It is clearly shown that when the average thickness ratio of the Si and Ni layers is 1:1, a large amount of strain is formed at the interface, which is in sharp contrast to the low strain results observed in Example 1. It can be seen that the 5:1 average thickness ratio design in the present invention is more advantageous.

[0159] Comparative Example 4:

[0160] The same as Example 1, except that the power density for preparing the Cr layer is 10.0 W / cm 2 , so higher power density will lead to higher sputtering rate and higher energy particles bombarding the substrate, which may promote more nucleation and irregular growth, thereby increasing large-angle grain boundaries and fewer small-angle grain boundaries, resulting in increased internal stress.

[0161] Performance Test:

[0162] Reflectivity: The reflectivity of the high reflective layer is tested using a Fourier spectrometer with a test band of 300-2500 nm, covering the visible light and near-infrared regions. The test uses a specular reflection accessory with an incident angle of 10° and a resolution better than 4 cm. -1 , each sample was scanned at least 32 times to improve the signal-to-noise ratio. During the test, attention should be paid to controlling the ambient temperature and humidity, calibrating the instrument regularly, and considering the uniformity and polarization sensitivity of the sample.

[0163] Internal stress: X-ray stress determination is an effective method to test the internal stress of the high reflective layer, which is measured by X-ray diffractometer. The test uses a Cu Kα radiation source with a wavelength of 1.5406 Å and a scanning range of 2θ = 20°-80°. The sin²ψ method is used to calculate the stress by measuring the change in the interplanar spacing at different tilt angles ψ. The test parameters include: tube voltage 40 kV, tube current 40 mA, step length 0.02°, and counting time of 2 seconds per step. At least 5 different ψ angles (in the range of 0°-60°) are selected for measurement. The data analysis uses the linear regression method to calculate the residual stress based on the slope of the d-sin²ψ graph. During the test, attention should be paid to the cleanliness of the sample surface to avoid surface contamination affecting the measurement results. At the same time, considering that the high reflective layer may have a texture effect, measurements are performed at different orientations of the sample to evaluate the anisotropy of stress. In order to improve the measurement accuracy, a high-resolution detector and a precise optical system are selected. The test report should include detailed instrument parameters, test conditions, stress calculation process, and measurement uncertainty analysis.

[0164] The performance of the high reflective layers in Examples 1 to 4 and Comparative Examples 1 to 4 are summarized in Table 1.

[0165] Table 1 Test results of high reflective layer performance of Examples 1 to 4 and Comparative Examples 1 to 4

[0166] ;

[0167] The main difference between Comparative Example 1 and Example 1 is that γ-Al 2 O 3 As can be seen from Table 1, when γ-Al 2 O 3 The (001) crystal plane of the substrate is perpendicular to the γ-Al 2 O 3 When the substrate surface is 2 O 3 The substrate can significantly improve reflectivity and reduce internal stress. This is because the oriented γ-Al 2 O 3 The (001) crystal plane provides a more ordered crystal structure foundation for the growth of subsequent layers, promoting more uniform and ordered film growth, thereby reducing the generation of defects and stress. At the same time, a more ordered structure is also conducive to improving the optical properties of the reflective layer, so the reflectivity is improved.

[0168] The main difference between Comparative Example 2 and Example 1 is that γ-Al 2 O 3Average surface roughness of the substrate. As can be seen from Table 1, a lower average surface roughness of the substrate can significantly improve reflectivity and reduce internal stress. This is because a lower average surface roughness provides a smoother growth substrate, which is conducive to the uniform deposition and growth of subsequent layers. The smooth interface reduces scattering and absorption, thereby improving reflectivity. At the same time, a smooth growth surface also reduces local stress concentration, which helps to reduce overall internal stress.

[0169] The main difference between Comparative Example 3 and Example 1 is the average thickness ratio of the Si layer and the Ni layer. As can be seen from Table 1, the average thickness of the Si layer and the Ni layer is 5:1, which can significantly improve the reflectivity and optimize the internal stress. This is because the average thickness of the Si layer and the Ni layer is 5:1, which can reduce the thermal mismatch stress in the preparation process, which is beneficial to the interference and reflection of light. At the same time, this specific average thickness ratio may better match the thermal expansion coefficient and lattice constant of the two materials, thereby achieving a better stress balance in the multilayer structure. In addition, appropriately increasing the average thickness of the Si layer may help to form a smoother interface, reduce interface scattering, and further improve the reflectivity. This optimized average thickness ratio not only improves the optical performance, but also may reduce the overall internal stress by reducing interface defects and stress concentration points, thereby improving the overall performance and stability of the high reflective layer.

[0170] The main difference between Comparative Example 4 and Example 1 is the power density for preparing the Cr layer. As can be seen from Table 1, a lower power density can significantly improve the reflectivity and reduce the internal stress. This is because a lower power density (3.0~6.0W / cm²) can reduce the bombardment of high-energy particles on the growing film during the sputtering process compared to a high power density of 10.0W / cm², thereby reducing the generation of defects. A lower power density is also conducive to forming a more compact and uniform Cr layer structure, reducing the formation of high-angle grain boundaries, and increasing the proportion of low-angle grain boundaries. This not only helps to reduce internal stress, but also improves the optical properties of the film, thereby improving the reflectivity.

[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A patterned low internal stress high reflective layer, characterized in that: The high reflective layer includes an n(Si / Ni) layer, a Cr layer, a cap layer, and a patterned reflective layer which are sequentially located on the γ-Al2O3 substrate from bottom to top; The n (Si / Ni) layer is composed of Si layers and Ni layers deposited alternately for n periods, and the alternating period n is 30 to 60; The average thickness of the Si layer is 15-40 nm, the average thickness of the Ni layer is 3-8 nm, and the average thickness ratio of the Si layer to the Ni layer is 5:1; the bottom layer of the n (Si / Ni) layer is a Si layer connected to the γ-Al2O3 substrate, and the top layer is a Ni layer; The average thickness of the Cr layer is 20-60 nm; the Cr layer contains low-angle grain boundaries; the content of the low-angle grain boundaries in the Cr layer is 45-65 vol%; The capping layer is RuNb, and the average thickness of the capping layer is 2-8 nm; The patterned reflective layer is CrCON, and the average thickness of the patterned reflective layer is 4-10 nm.

2. The patterned low internal stress high reflective layer according to claim 1, characterized in that: A strain relaxation interface is contained between the Si layer and the Ni layer; The Ni layer contains a twin structure, and the twin structure is grown by releasing the interface stress of the strain relaxation interface between the Si layer and the Ni layer; the density of the twin structure is (4-10)×10 7 cm -1 .

3. The patterned low internal stress high reflective layer according to claim 1, characterized in that: The (001) or (111) crystal plane of γ-Al2O3 in the γ-Al2O3 substrate is perpendicular to the surface of the γ-Al2O3 substrate; The average surface roughness of the γ-Al2O3 substrate is Ra<2 nm.

4. The patterned low internal stress high reflective layer according to claim 3, characterized in that: The preparation method of the γ-Al2O3 substrate is as follows: using a Si wafer as a substrate, wherein the Si wafer is a Si(001) wafer or a Si(111) wafer, firstly obtaining a γ-Al2O3 substrate on the Si wafer by a molecular beam epitaxy method, and then sequentially preparing the γ-Al2O3 substrate by acid etching and chemical mechanical polishing; The preparation parameters of the molecular beam epitaxy method are as follows: at 600-750°C, with Al as the target material, with a flow rate of 30-60 sccm and a purity of 99.99% oxygen as the reaction atmosphere, a radio frequency plasma source power of 50-100 W, and a working pressure of (1-5)×10 -4 Pa, obtain γ-Al2O3 substrate on Si wafer; The acid etching comprises the following steps: placing the γ-Al2O3 substrate on the Si wafer into a hydrofluoric acid solution with a mass fraction of 50-55% to etch the Si wafer, washing the γ-Al2O3 substrate with deionized water after the etching is completed, and finally completely drying it in vacuum at room temperature.

5. A method for preparing a patterned low internal stress high reflective layer as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1, firstly perform ultrasonic cleaning on the γ-Al2O3 substrate, then use acetone and deionized water to clean it, and finally blow dry the surface of the γ-Al2O3 substrate with high-purity nitrogen; S2, placing the γ-Al2O3 substrate obtained in step S1 into an ultra-high vacuum magnetron sputtering system, with a basic vacuum degree of less than 5×10 -8 Torr, the chamber temperature is 25 ± 2°C; S3, using magnetron sputtering method, Si layer and Ni layer are alternately deposited on the γ-Al2O3 substrate in sequence, the number of alternating deposition cycles is n, and n (Si / Ni) layers are formed; S4, preparing a Cr layer on the n(Si / Ni) layer by magnetron sputtering; S5, preparing a cap layer on the Cr layer by magnetron sputtering; S6. Prepare a reflective layer to be patterned on the cap layer by magnetron sputtering, then coat and pattern the reflective layer to be patterned with photoresist, and then etch the reflective layer to be patterned with an etching solution to obtain a patterned reflective layer; and then perform vacuum annealing at 200-250° C. for 1 hour.

6. The preparation method according to claim 5, characterized in that: The preparation parameters of the Si layer in step S3 are: using Si with a purity of 99.999% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 15-40 sccm, and the sputtering power density to 1.5-3.0 W / cm 2 ;Deposition rate is 0.20~0.50 nm / s; The preparation parameters of the Ni layer in step S3 are: using Ni with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 25-60 sccm, and the power density to 2.0-4.0 W / cm 2 ;Deposition rate is 0.15~0.30nm / s; The preparation parameters of the Cr layer in step S4 are: using Cr with a purity of 99.95% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 20-40 sccm, and the power density to 3.0-6.0 W / cm 2 ; The deposition rate is 0.50~0.90 nm / s.

7. The preparation method according to claim 5, characterized in that: The preparation parameters of the cap layer in step S5 are: using RuNb with a purity of 99.99% as the target material, adjusting the flow rate of 99.999% high-purity argon gas to 20-45 sccm, the sputtering power to 100-200 W; the deposition rate to 0.05-0.20 nm / s, the sputtering working pressure to 0.5-1.5 Pa, and the sputtering temperature to 120-180° C.; The preparation method of the reflective layer to be patterned in step S6 is: adopting a magnetron sputtering method, using Cr with a purity of 99.95% as a target material, and using a mixed gas of argon with a purity of 99.999%, nitrogen with a purity of 99.999%, oxygen with a purity of 99.999% and methane with a purity of 99.999% as an atmosphere, wherein the volume ratio of argon, nitrogen, oxygen and methane is 4:1:1:0.5, the flow rate of the mixed gas is 25~50sccm, the sputtering power is 150~300W, the sputtering working pressure is 0.5~1.5Pa, the sputtering temperature is 150~200℃, and the substrate bias is 10~35V.

8. Use of the patterned low internal stress high reflective layer according to any one of claims 1 to 4 in the field of photolithography mask, optical imaging or sensor.

Citation Information

Patent Citations

  • EUV photomask and manufacturing method thereof

    CN113267956A

  • Vertical-structure LED chip for preparing Ag reflector by using two-step method and preparation method of LED chip

    CN108336197A

  • Patterned high-reflection layer with good adhesive force as well as preparation method and application of patterned high-reflection layer

    CN118957528A